Improving the Provisions on Enforcement of Intellectual Property Rights in Order to Implement Vietnam’s Commitments in the New-Generation Free Trade Agreements - Thao, Nguyen Bich (VNU Journal of Science: Legal Studies; Vol 38 No 3, 2022)
The Law on amending and supplementing a number of provisions of the Law on Intellectual Property, which was passed by the National Assembly on June 16, 2022, has marked a new development stage of Vietnam’s intellectual property law in the process of international integration with the incorporation of many commitments of Vietnam in the new-generation free trade agreements, including strong commitments on enforcement of intellectual property rights. This article analyzes the formulation and development of international standards on enforcement of intellectual property rights, focusing on the new provisions of new-generation free trade agreements on enforcement of intellectual property rights compared to those under the TRIPS Agreement of the World Trade Organization. From there, the article compares these international standards with the Law on amending and supplementing a number of provisions of the Law on Intellectual Property and makes recommendations to continue improving Vietnamese intellectual property law on enforcement of intellectual property rights.